Intuitionistic Fuzzy Soft Near Rings Induced by \((T,S)\)-norms - Varol, Banu Pazar; Aygün, Halis (Communications in Mathematics and Applications, 2020)
In this work, we combine the near ring concept and intuitionistic fuzzy soft set. By using \(t\)-norm and \(t\)-conorm we define intuitionistic fuzzy soft near ring over a given classical near ring and study its characteristic properties.